Enhanced thermoelectric performance of Cu2ZnSnS4 (CZTS) by incorporating Ag nanoparticles. Issue 2 (1st February 2019) - Sharma, Sarita Devi; Khasimsaheb, B.; Chen, Y.Y.; Neeleshwar, S.
Abstract: Thermoelectric properties of Cu2 ZnSnS4 (CZTS) microspheres on addition of Ag nanoparticles in different weight percentage (0, 0.5%, and 1%) were investigated in the temperature range from 300 K to 623 K. CZTS/Ag thermoelectric composites were fabricated by mixing the CZTS powder synthesized by microwave method and silver nanoparticles (Ag NPs) followed by hot pressing at 623 K. Due to the addition of highly conductive Ag NPs in the composites, the electrical conductivity increased systematically from parent sample value of 852 Sm −1 to the values of CZTS/0.5 wt% and CZTS/1 wt% composites which were 4291 Sm −1 and 6369 Sm −1 respectively at room temperature while maintaining moderate Seebeck coefficient. Improved power factor values (117 µW/mK 2 and 84.6 µW/mK 2 ) for the CZTS/ (0.5, 1 wt%) Ag composites compared to bare sample (55 µW/mK 2 ) were observed at 623 K. Besides, a lower thermal conductivity (~0.42 W/m K) for CZTS/0.5 wt% Ag composite in comparison to the bare sample (~0.49 W/m K) at 623 K was also obtained due to phonon scattering by dispersed Ag NPs. It was observed that CZTS/0.5 wt% Ag sample exhibited a figure of merit 0.17 at 623 K almost 2.5 times more than parent CZTS sample (0.069), which was attributed to the improvement in the electrical conductivity and reduction in the total thermal conductivity. These results demonstrate that addition of Ag NPs into the CZTS host material has a potential to enhance the thermoelectric performance. Graphical abstract: